Which Measures and Parameters of Heart Rate Variability Analysis may be Useful for Early Detection and Predicting Prognosis of Sepsis? A Systematic Review - Hasan Kazdağlı; Hasan Fehmi Özel (Türk Yoğun Bakim Derneği Dergisi)
Sepsis causes a series of pathological changes, such as cardiovascular, respiratory, and thermoregulation. These changes alter heart rate variability (HRV). Even without any changes in the vital signs or clinical presentation of the disease, HRV may still be altered due to sympathetic nervous system activation caused by infection. Our aim in this review was to present sepsis-related HRV measures and parameters by examining the literature and their possible role in predicting the severity and mortality of sepsis. Databases were searched for original research articles reporting on human HRV-related sepsis published in the English language between April 1996 and May 2023. After completion of the article search, a total of 79 articles were selected for further evaluation where the full text of the articles was reviewed and 13 of the articles met the criteria for inclusion. The mean values of each HRV parameter were corrected to the sample size of each study, and the overall means were calculated accordingly. Statistical comparisons were performed after correcting for sample size using the Willcoxon signed-rank test. After the final evaluation, with a total of 1453 patients, 9 studies on sepsis in humans were included. The weighted mean age was 64.24 years, and 53.9% were male. Of the studies included, all underwent frequency domain analysis, and four underwent non-linear analysis. Seven of the nine studies were conducted in the emergency departments, and two were conducted in the intensive care units. 6 studies compared parameters between survivors and non-survivors, and 3 studies compared parameters between different severity levels of sepsis. SDNN, RMSSD, SDNN, HTI, LFnu, HFnu, LF/HF ratio, SD1, SD2, detrended fluctuation analysis (DFA)α1, and DFAα2 appear to be related to mortality in patients with sepsis outcome. Therefore, monitoring these parameters for the early detection of sepsis may be beneficial.